PENDAMPINGAN APLIKASI INSEKTISIDA DARI KULIT BIJI JAMBU METE DI DESA JENGGRIK, KECAMATAN KEDUNGGALAR-KABUPATEN NGAWI - Andayanie, Wuye Ria; Puspitawati, Indah Rekyani; Wardhani, Ratna Mustika (UNIVERSITAS PGRI MADIUN, 2024)
Abstract. Cashew nut shells are waste from cashew seed processing. Cashew nut shells contain anacardic acid compounds from the flavonoid group and have high biodegradability, making them environmentally friendly for pesticides. The mentoring activity aims to improve farmers' skills in producing and applying vegetable insecticides for soybean plants from cashew nut shells. The mentoring activity method is carried out using a Participatory Rural Appraisal (PRA) pattern with soybean farmer partners who are members of the farmer group (Gapoktan)